Mangrove Structure and Composition Analysis in Teluk Jor, East Lombok Regency - Akbar, Lalu Faraby Alif; Idrus, Agil Al; Mahrus, Mahrus; Santoso, Didik (Jurnal Biologi Tropis, 2024)
The presence and sustainability of mangrove plants can be inferred from the species' composition and organization within a forest region. The goal of this study is to ascertain the environmental conditions of the mangrove ecosystem in the Teluk Jor region of East Lombok Regency, as well as the diversity index of mangrove species and the structure and composition of the mangrove vegetation. Purposive sampling is used in this descriptive exploratory study design, and data is gathered utilizing transects and quadrants. The results of the research found 7 types of mangroves with 4 families namely the rhizophoraceae family (Rhizophora mucronata, Rhizophora apiculata and Ceriops tagal), the sonneratiaceae family (Sonneratia alba and Sonneratia caseolaris), the avicenniaceae family (Avicennia marina) and the combretaceae family (Lumnitzera racemosa). Sonneratia alba has a relative frequency (FR) value of 63.16%, relative density (KR) of 80.33%, and the highest relative dominance of 78.84% followed by Rhizophora apiculata, Sonneratia caseolaris and Avicennia marina. Seven mangrove species and four families with the greatest important value index belong to Sonneratia alba, according to the research's findings. The sapling category's diversity index was categorized as medium, while the tree category's diversity index was categorized as low.